2011
DOI: 10.1089/jmf.2010.1428
|View full text |Cite
|
Sign up to set email alerts
|

The Biflavonoid Amentoflavone Induces Apoptosis via Suppressing E7 Expression, Cell Cycle Arrest at Sub-G1Phase, and Mitochondria-Emanated Intrinsic Pathways in Human Cervical Cancer Cells

Abstract: Amentoflavone, a biflavonoid from Selaginella tamariscina, is known to possess several bioactivities such as antitumor, anti-inflammatory, and antifungal effects. However, the mechanism of the anticancer effects of amentoflavone on human cervical cancer cells has not been studied in detail. In this study, we demonstrated that amentoflavone induces apoptosis in SiHa and CaSki cervical cancer cells by suppressing human papillomavirus protein E7 expression. The cyclins and tumor suppressors were modulated by amen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…Thus, ultraviolet radiation was proved to cause several human cancers [22][23], especially skin cancer [24] and breast cancer [22][23][24][25]. In the study, however, amentoflavone was observed to be a treating agent for the carcinogenesis [26][27]. Therefore, it can be induced that the anti-cancer effect of amentoflavone could be partly attributed to its protective effect against DNA oxidative damage and antioxidant mechanism.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, ultraviolet radiation was proved to cause several human cancers [22][23], especially skin cancer [24] and breast cancer [22][23][24][25]. In the study, however, amentoflavone was observed to be a treating agent for the carcinogenesis [26][27]. Therefore, it can be induced that the anti-cancer effect of amentoflavone could be partly attributed to its protective effect against DNA oxidative damage and antioxidant mechanism.…”
Section: Resultsmentioning
confidence: 93%
“…It displayed an [M-H] − ion peak at m/z 404.9 and its molecular formula of C 22 (Tables 1 and 2) of 4 also showed 1,2,5-trisubstituted benzene ring and the apigenin skeleton structure, implying compound 4 and compounds 1-3 were classified into same class of compounds. Compounds 1-3 had an α, β-unsaturated ketone group located at C-5″ in their structures, however, the corresponding NMR signals were not observed in compound 4, which was suggested by the reduction of unsaturation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous phytochemical studies of S. uncinata led to the discovery of flavonoids [15][16][17], biflavonoids [18], chromone glycosides [19], and steroidal saponins [20]. Those compounds have a range of biological activities such as antitumor [21,22], antibacterial [19], antioxidation [23] and anti-anoxic [18,20]. As part of our continuing research program on these plants, chemical investigation of 75% EtOH extracts of S. uncinata was undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Based on selected published studies, it was hypothesized that restoration of sorafenib-induced apoptosis by sensitizers is critical in overcoming acquired sorafenib resistance in HCC cells. Amentoflavone has been demonstrated to inhibit tumor growth through induction of apoptosis in breast and cervical cancer cells (14,15). However, whether amentoflavone is able to act as a sorafenib sensitizer, which restores sorafenib-induced apoptosis in sorafenib-resistant HCC cells, has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Amentoflavone, as a NF-κB signal inhibitor, induces anti-angiogenic and anti-metastatic effects via suppression of NF-κB activation in breast cancer and melanoma cells in vitro and in vivo (11,12). Amentoflavone has also been suggested to induce apoptosis and inhibit Akt phosphorylation in cervical and breast cancer cells (14,15). However, whether amentoflavone, as a sorafenib sensitizer, triggers sorafenib-induced apoptosis in sorafenib-resistant HCC cells remains ambiguous.…”
Section: Amentoflavone Enhances Sorafenib-induced Apoptosis Through Ementioning
confidence: 99%